Student Perceptions to Implementation Independent Practicum based of Materials in The Environment - Ita Ita; Hadijah Hadijah (Bioeducation Journal, 2022)
COVID-19 pandemic had a major impact on the implementation of the teaching process. Lectures suddenly switched from face-to-face to online, including practical courses. This system change certainly has its own impression for students, especially for those who program practicum courses. Research was conducted with quantitative approach through questionnaire and qualitative one through interviews with descriptive analysis technique. The purpose of this study was to describe students' perceptions of implementation material-based independent practicum in surrounding environment. The results showed that aspect of ease independent practicum 22.92% of students had perception of strongly agreeing, 43.75% agreeing, 33.32% disagreeing, and 0% strongly disagreeing. Aspect of ease understanding concept perception who strongly agree as much as 18.33%, agree with the presentation 74.17%, 7.5% disagree, and strongly disagree with percentage of 0%. Finally, on aspect of satisfaction in practicum, it was stated that 14.58% of students strongly agreed, agreed 63.19 while those who disagreed were 22.22% and strongly disagreed 0%. Students have perception that practicum is carried out independently in their respective residences can still run smoothly. This is because materials used are relatively easy to find in the surrounding environment. Online guidance provided also makes it easier to ask questions. Literature provided during independent practicum process also makes it easier to do practicum and understand procedure. In conclusion, average dominant student answers agree that independent practicum from home based materials in surrounding environment is relatively easy to do, it is also easy to understand concept and students are satisfied in implementation of independent practicum.